Generalized lymphadenopathy in patient with fever of unknown origin as a differential diagnostic challenge - case report - Sofija Sekulic Markovic; Ivana Rakovic; Sara Petrovic; Dusica Petrovic Rodic; Nenad Zornic; Biljana Popovska Jovicic (Journal of the Pakistan Medical Association, 2021)
Published in May - 2021